‘Adam Al-Haraj: Aplikasi Rukhshah dalam Implementasi Hukum Islam dalam Kehidupan Masyarakat Modern - Bunyamin, Mahmudin (al-'adalah, 2018)
One of the principles of Islamic teachings is to ease people’s lives or to eliminate the difficulty. If in a certain occasion, people find it difficult (masyaqqah) to perform any obligations, Islam then gives a relief (rukhshah). For instance, when Muslims are travelling (safar) with a certain distance, they will get any easiness for their obligations, such as prayer. However, there is condition for the easiness. Given to the two situations, first people who travelling by air plane with hundred kilometers distance are comfortable because of the plane and they can travel fast. Another situation is people spending for ages because of the traffic jam are exhausting because of long journey. Those people who travel by plane are eligible to obtain rukhshah because they travel with hundred kilometers distance, while those who are stuck in the traffic jam are not. These situations absolutely need to be investigated.